Assessing Carrying Capacity of Marine Aquaculture in Pangkil Island, Bintan, Indonesia - Dedy Kurniawan; Wahyudin Wahyudin; Dwi Septiani; Aidil Fadli Ilhamdy; Jumsurizal Jumsurizal; Aulia Rahman; Ulia Fahmi; T Ersti Yulikasari (Journal of Marine and Coastal Science, 2022)
Pangkil is a small island in Indonesia with huge fisheries production where the majority of citizens' livelihoods are fisherman. The decline of fisheries catch production has led to aquaculture activity increasing year by year. Environmental conditions are the most important consideration for marine aquaculture sites. The aims of the present study are to estimation of the carrying capacity in Pangkil island water for marine aquaculture. The study was carried out in January 2020 at 30 locations. To describe the environmental condition, 30 samples were collected to analyse the physical, chemical, and biological parameters. To estimate the carrying capacity, suitability index was applied. The result showed that 57.13% of environmental conditions have very suitable for marine aquaculture (sea cage) in Pangkil Island, while 42.87% is only quite appropriate. Based on the result, Pangkil Island water has high potential for marine aquaculture in the future.